Peptides in breast milk and their benefits for children - Aydin, S. (Wageningen Acad Publ, 2013)
Human milk is a unique complex biological fluid containing many nutrients, including peptide hormones. These peptides are either passed from the blood into the milk, or synthesized in the mammary gland and secreted in the milk. Several human milk peptides have fewer than 50 amino acid (aa) residues: oxytocin, ghrelins, obestatin, pituitary adenylate cyclase activating polypeptide, apelins, motilin, copeptin. Others comprise more than 50 aa: insulin, nestfatin-1, resistin, leptin, prolactin, adiponectin and visfatin. They are associated with a variety of biological functions such as regulation of metabolic pathways, feeding, influence on bone formation, fluid regulation, stimulation of learning, growth hormone release, regulation of sleep, regulation of appetite, neuropsychiatric manifestations, regulation of lipolysis in adipocytes, regulation of lactation, short-and long-term body-weight regulation, postnatal growth and development of different organs in the newborn. Normal physiological concentrations of milk peptide hormones promote the normal development of the infant, while abnormal concentrations during a critical period may lead to suboptimal development of fundamental regulatory systems in babies. Peptides obtained from breast milk (exogenous peptides) might have similar functions to endogenous peptides in the neonate's circulation, especially those such as ghrelin and oxt that resist proteolytic degradation in the gastrointestinal tract. The purpose of the following chapter is to examine the most recent findings concerning human breast milk peptide hormones by classifying them into two groups - peptides comprising up to 50 aa residues and peptides comprising more than 50 aa - and considering their potential influence on children.
Keywords: peptides; influences on children